Effects of Consuming Repeatedly Heated Edible Oils on Cardiovascular Diseases: A Narrative Review - Soundararajan, Prathyusha; Parthasarathy, Srividya; Sakthivelu, Meenakumari; Karuppiah, Kanchana Mala; Velusamy, Palaniyandi; Gopinath, Subash Chandra Bose; Raman, Pachaiappan (Current Medicinal Chemistry, 2024)
Edible oils are inevitable requisites in the human diet as they are enriched with essential fatty acids, vitamins, carotenoids, sterols, and other antioxidants. Due to their nutritive value and commercial significance, edible oils have been used for food preparation for many centuries. The use of global consumption of edible oils has dramatically increased throughout the world in the 21st century owing to their incredible application in all kinds of food preparation. However, a variety of pollutants, such as pesticides, toxic chemicals, heavy metals, and environmental pollution, have contributed to the contamination of edible oils. Furthermore, the benzophenanthridine alkaloids, sanguinarine, dihydrosanguinarine, butter yellow, and other several agents are added intentionally, which are known to cause a number of human diseases. Apart from this, repeated heating and reusing of oils results in trans fats, and lipid peroxidation alters the fatty acid composition, which adversely affects the health of consumers and increases the risk of cardiovascular diseases. Moreover, the prevention of edible oil contamination in human health at various levels is inevitable to ensure consumer safety. Hence, the present review provides an overview of vegetable cooking oils and the health ailments that detection techniques are focused on.
Keywords: cooking oil